2011
DOI: 10.1007/s11069-011-9950-1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of seawater inundation along Nagapattinam based on field observations

Abstract: Nagapattinam, in the east coast of India, was severely affected during the deadliest Indian Ocean tsunami of December 26, 2004. The tsunami caused heavy damage to life and property, and the death toll was about 3,378 in Nagapattinam taluk. Certain villages along the coast witnessed large inundation while adjacent villages were protected from the fury of the tsunami waves. This study was carried out to examine the underlying causes for the vulnerability along Nagapattinam coast with the help of field observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Storm debris [77,78] and tidal deposits [79] can be used as water level limit and maximum runup extent indicators. A field survey was conducted on the day of, and immediately following, the 6 December 2010 flood event, in order to identify maximum flood water levels reached at Maria (Figure 3a).…”
Section: Post-storm Surveysmentioning
confidence: 99%
“…Storm debris [77,78] and tidal deposits [79] can be used as water level limit and maximum runup extent indicators. A field survey was conducted on the day of, and immediately following, the 6 December 2010 flood event, in order to identify maximum flood water levels reached at Maria (Figure 3a).…”
Section: Post-storm Surveysmentioning
confidence: 99%
“…Storm debris (Mather et al 2010;Ramana Murthy et al 2012) and tidal marks or deposits (Cariolet and Suanez 2013;Guimarães et al 2015;Suanez et al 2015) can be used as water level limits and runup extent indicators. In this paper, we consider maximal runup (R max ) according to the following expression:…”
Section: Post-storm Measurements Of Flood Debris and Topographic Surveysmentioning
confidence: 99%
“…These types of tsunami waves can cause massive damage or failures to coastal structures (Kato et al, 2007). From the field surveys after the 2004 Indian Ocean and 2011 Japanese tsunami, it was revealed that natural coastal features such as dunes, dense vegetation, and a combination of dunes with vegetation, acted as natural buffers and provided protection to infrastructure and communities further landward (Fritz and Borrero, 2006;Wijetunge, 2006;Murthy et al, 2012;Wijetunge, 2012). The role of coastal forests, such as mangrove vegetation, on tsunami run-up and inundation reduction, have been extensively studied by many researchers with physical and numerical modeling (Husrin et al, 2012;Yao et al, 2015;Esteban et al, 2017), but not the influence of coastal dunes in offering direct protection.…”
mentioning
confidence: 99%
“…Numerous studies from tsunami field surveys state that coastal dunes shielded their respective neighbourhoods from the disastrous impact of the tsunami (Jayakumar et al, 2005, Murthy et al, 2012. Data from field studies have identified that removing coastal natural protection for public practice, such as mangrove vegetation and dunes, increases the impact of tsunami (Chang et al, 2006;Wijetunge, 2006).…”
mentioning
confidence: 99%